Women in Afircan Development the challenge of globalization and liberalization in the 21st century - Boko, Sylvain H. (Asmara Africa World Press, 2005)
The basic premise of this book is that one of the most effective ways to ensure increased and sustainable development in Africa is through the improvement of Afircan women's skills and ensuring their access to tools such as as credit, training, and the technology. Understanding and supporting the potentialities of African women in the context of new economic realities facing Africa (i.e. globalisation) is crucial to the future of Africa's economic development. However, political,legal and cultural impediments to women's full participation in economic and political life remain in place in many, if not most, African countries. Thus, strategies designed to overcome such impediments to women's full participation in economic and political life are crucial to the future of Africa. This book is the first of its kind to analyze and bring to the forefront of policy-making the linkages that exist between globalization and the role of women in development in Africa. These essays put an emphasis on practical solutions to the issues raised throughout the book. Furthermore, the book stands to become a policy manual,which will help to disseminate the strategies, conclusions, and recommendations that emanated from the variety of research presented, to a diversity of audiences, including NGOs, national and international government agencies, businesses, women's groups, internationa educational organisations, as well as academic institutions and multilateral financial institutions.
Includes index
Keywords: Women in development-Africa, Women-Africa-Economic conditions Women-Africa-Social conditions